RAHIMA AMINOVANING XOTIN-QIZLAR IJTIMOYLASHUVIDAGI ILMIY IZLANISHLARI (Scientific journal of the Fergana State University, 2026)
This article explores the contribution of renowned Uzbek historian Rahima Aminova to national historiography, particularly her research on women's social integration and their role in society. The author highlights Aminova’s scholarly legacy, including her analysis of the legal and social limitations faced by Uzbek women during the Soviet era. Special attention is given to her publication "Urgent Problems of Social Development in Uzbekistan during Perestroika", which addresses issues such as social injustice, regional disparities, and the undervaluation of women’s labor. Aminova’s active participation in international conferences, her fluency in English, and her role in mentoring young scholars are emphasized. Her extensive academic work and the scholars she trained continue to serve as a valuable resource for contemporary researchers. The article underlines the lasting relevance of Rahima Aminova’s academic legacy and its importance in shaping both current and future understandings of historical and social development in Uzbekistan.